2020
DOI: 10.3390/ijms21165834
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Clinicopathological Significance of MiR-155 in Breast Cancer: A Systematic Review

Abstract: There is an unmet need for novel non-invasive prognostic molecular tumour markers for breast cancer (BC). Accumulating evidence shows that miR-155 plays a pivotal role in tumorigenesis. Generally, miR-155 is considered an oncogenic miRNA promoting tumour growth, angiogenesis and aggressiveness of BC. Therefore, many researchers have focused on its use as a prognostic biomarker and therapeutic target. However, its prognostic value for BC patients remains controversial. To address this issue, the present systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 43 publications
(96 reference statements)
1
9
0
Order By: Relevance
“…We excluded the fat mass index variable, to avoid collinearity with weight and visceral fat. On the multivariate model, we decided to include the variables of molecular classification of the tumor, ER positive, and LDL cholesterol due to their previously reported association with the expression of miRNA-155 [ 38 ] and fat mass in patients with breast cancer; additionally, we included variables whose p -value was close to 0.2 ( Table 2 ). The multivariate model showed that visceral fat (negative) and Ki67 (positive) were significant, and when combined, they formed the best association model ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…We excluded the fat mass index variable, to avoid collinearity with weight and visceral fat. On the multivariate model, we decided to include the variables of molecular classification of the tumor, ER positive, and LDL cholesterol due to their previously reported association with the expression of miRNA-155 [ 38 ] and fat mass in patients with breast cancer; additionally, we included variables whose p -value was close to 0.2 ( Table 2 ). The multivariate model showed that visceral fat (negative) and Ki67 (positive) were significant, and when combined, they formed the best association model ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…To date, just a few miR-based therapeutics are actually under Phase-I clinical trials for oncological diseases (see Table 3 ), such as Cobomarsen and TargomiR, both developed by miRagen Therapeutics. Cobomarsen, (also known as MRG-106) is an inhibitor of miR-155, an oncomir highly expressed in a wide range of cancers, including BC ( 44 ). Two clinical trials are ongoing in Phase I, to evaluate the safety of this drug for the treatment of adult patients diagnosed with certain lymphomas and leukemias (NCT02580552 and NCT03713320).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in the literature that the overexpression of miR-155 could be a diagnostic target for breast cancer. 29 It suggests that the delivery of the miR-155 inhibitor (anti-miR-155) may hold the potential for breast cancer therapy. We firstly evaluated the transfection efficiency of anti-miR-155 loaded polyplexes in 4T1 cell lines.…”
Section: Papermentioning
confidence: 99%